ASSESSING INSTITUTIONAL COMPETENCIES OF ECOTOURISM; SPECIAL REFERENCE TO THENMALA ECOTOURISM PROJECT KERALA, INDIA - A, VINODAN (ASEAN Journal on Hospitality and Tourism, 2010)
Ecotourism is an approach to tourism development to meet the sustainable development initiative globally. In order to meet the sustainability through resource appropriation a clear and well-knitted framework is very essential. The present study made a detailed investigation on destination management with reference to Thenmala Ecotourism Project, India’s first planned ecotourism. Further, it evaluates the competencies of institutional arrangements to meet the policy objectives of ecotourism through SWOT analysis of the destination. The study shows that the destination level framework is (a). Thenmala Ecotourism Promotion Society (TEPS) at the administrative level and (b) community based organizations like Eco Development Committees (EDC) under Forest Development Authority (FDA) and Self Help Groups (SHG) under Kudumbashree Programme at the operational level which have certain operational weakness leading to sustainability failures. Study further suggests for an integrated efforts to revitalize these grass root level institutions.